The social topology of science in national and transnational contexts: the case of social sciences - Nedelevskaya, Ilona G. (Journal of the Belarusian State University. Sociology, 2021)
The article explores the possibilities of application P. Bourdieu’s social topology in the studying of inequality in science in national and transnational contexts. It is argued that in the conditions of globalising science, discussions about its egalitarianism, which began approximately in the middle of the last century, are moving beyond national borders. For the purposes of studying global inequality in science, scholars often apply the theoretical frameworks of world-systems analysis, neo-institutionalism, and the theory of global governance. However, these theories often lead to reductionism which ignores the symbolic dimension of scientific activity. The article suggests reassessing the heuristic potentiality of P. Bourdieu’s social topology, which mitigates the mentioned drawback of other theories. The article aims to demonstrate the relevance of this theoretical framework for the study of inequality in different scales of scientific activity due to the fact that the French sociologist focused mainly on national academic systems. The article defines the general provisions of P. Bourdieu’s topological concept of the field and the units of the social order of the scientific field. It also demonstrates the role of various forms of capital in determining the structure of social space. Based on the case of social sciences, the article explores the formation of scientific fields, their interaction with other fields, and their structure in different scales. The structure of the scientific field on the national scale can be defined as a dichotomy of dominant – dominated or centre – periphery. On the transnational scale, this dichotomy is also relevant but it is represented by national fields. Among them, the dominant position is occupied by the United States and Great Britain, which have the largest amount of symbolic power. The structure of the transnational scientific space, however, is more complex and includes overlapping fields of national, regional and more global dimensions. The article argued that applying the theoretical framework of the field to the study of the transnational scientific field will remain tied to the definition and explanation of the peculiarities and the interaction of national scientific fields as long as national states keep their institutional boundaries in scientific activity.